PENDAPATAN RUMAH TANGGA MANTAN PELAKU ILLEGAL LOGGING TAMAN NASIONAL MERU BETIRI JEMBER - Ihsannudin Ihsannudin; Mohamad Wisnu Mukti (Center for Economic Studies Universitas Katolik Parahyangan, 2024)
Meru Betiri National Park was one of the national parks in Indonesia which has the main function as a biodiversity conservation area. An area covering an area of 66,068.55 hectares is under threat from deforestation with the loss of forest cover covering an area of 3,382 hectares or 6.5% of the area, one of which is caused by illegal logging activities. Taking into account this condition, the Meru Betiri National Park Office is taking a preemptive approach through economic empowerment for the households of ex-illegal loggers. The aim of this research is to determine: 1) Household income of ex-illegal loggers, (2) differences in household income of ex-illegal loggers based on their type of income. The location of this research is Sanenrejo Village and Andongrejo Village, Tempurejo District, Jember Regency with 71 respondents from households of ex-illegal loggers. For the first objective of this research, quantitative descriptive analysis was used and for the second objective, the independent sample t test was used. According to the findings of this research, the average household income of ex-illegal loggers is IDR 2,384,823 per month. The household income of ex-illegal loggers from the agricultural and non-agricultural sectors has significant differences. This shows that non-agricultural income sources for ex-illegal loggers households have greater opportunities to be developed while still paying attention to non-agricultural sector income sources.